(untitled) (Research, Society and Development, 2020)
With technological development, the use of ICT (Information and Communication Technology) is increasingly present in the practice of teaching and learning, enabling several benefits, among them, greater flexibility and retains greater attention and involvement of the participant, such as it also benefits activities related to promotion and prevention. Thus, the objective was to develop an experiential and instructional resource as an innovative strategy for the promotion of hearing health, with regard to the use of personal stereos. The development of the instructional and experiential resource was carried out by three students of the Speech Therapy course, using the methodological approach of Design Thinking in the stages of immersion, ideation and prototyping. The Powtooon digital video creation platform was used, with two songs in Brazilian Portuguese acoustically manipulated through the Adobe Audition CC version 11.1 2018 platform. Two experiential resources and an instructional resource, in audio-visual format, were produced. The experimental resources were manipulated to remove the fricatives / f /, / v /, / s / and / z / simulating a hearing loss in the frequencies around 4 to 8kHz and 10 to 30dBHL, presenting associated tinnitus and decreased hearing acuity, with a feeling of “stuffiness”. A resource was developed under the experiential and instructional perspectives allowing the experience of listening to music with a simulated sensation of hearing loss / tinnitus and guidance on the use of personal stereos, with the possibility of promoting hearing health, with interaction, in order to enhance awareness, education about the use of earphone.